Optimal conditions for the fruit body production of natural occurring strains of Lentinus tigrinus - Lechner, Bernardo Ernesto (2007)
Lentinus tigrinus is a species with a fleshy pileus, strong odor and agreeable taste. In order to determine the optimal conditions for the production of this species, three substrates based on Salix sp. sawdust, wheat straw and supplements were tested in 500 g dry weight bags at two different fruiting temperatures. Naturally occurring strains of this species were incubated at 30 °C. Primordium initiation could be observed 11–16 days after induction conditions began. This species produced highest yields with biological efficiency (BE) of 62% with supplemented sawdust at 25 °C. When bags were reduced to 100 g dry weight, spawning run time was reduced from 28 to 30 to 10 to 14 days and BE increased more than 100%. L. tigrinus is a promising species with possibilities for commercial production.